Unmet Information Needs of Patients with Rheumatic Diseases: Results of a Cross-Sectional Online Survey Study in Germany - Becker, Christian; Diener, Matthias; Hueber, Axel J.; Henes, Joerg; Krusche, Martin; Ignatyev, Yuriy; May, Susann; Erstling, Ulrike; Elling-Audersch, Corinna; Knitza, Johannes; Muehlensiepen, Felix (International Journal of Environmental Research and Public Health, 2022)
To effectively self-manage a chronic disease, patients require specific education. In clinical routines, rheumatologists and other healthcare professionals often cannot devote the necessary time to adequately educate their patients. Digital technologies such as mobile applications represent promising tools to overcome this problem. This study aims to identify unmet information needs of patients with rheumatic diseases to inform the conception of a mobile education application. An online national survey was developed together with rheumatic patients and rheumatologists and distributed between June and September 2021 via social media (Instagram, Facebook, Twitter), QR code and email. Self-reported rheumatic patients, rheumatologists, specialized rheumatology nurses (SRN) and self-reported relatives of rheumatic patients were eligible to participate in the survey. Three major topics were addressed: (1) How well do patients feel informed about disease-relevant topics; (2) how important do patients rate different disease-relevant topics; and (3) patient willingness to adopt digital education services. Responses of 254 patients and 53 SRN were analyzed. Most patients were female (91%; n = 231), the median age was 48 years and the most common disease was rheumatoid arthritis (23%; n = 59). Only 24% of patients perceived their disease education level as very good or good compared to an SRN estimate of 42%. The three information topics rated as most important (very/important) were: individual disease (98%), medication (94%) and coping techniques (91%). In total, 89% of patients asserted that they would very likely, likely or rather likely use digital education tools in the future to learn about their condition, and 82% of SRN would very likely, likely or rather likely recommend digital information services to their patients. These findings depict currently unmet patient information needs and a high willingness of patients and SRN to use digital education services. A mobile education application is currently adapted based on these results and will be evaluated in a multicenter study.
CRIS-Team WoS Importer:2022-07-08